Design, construction and initial operation of a water re-use plug at New Afton Mine - Thomas, A.; Joughin, W.; Khalil, H.; Owre, S.; Yanagimura, Y. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Mining operations often require sealing of underground openings for range of reasons. At New Afton mine, a plug was conceptualised to impound water for the purpose of underground water re-use and to route water to existing water management infrastructure. This paper describes the advancement of this concept through to design, construction and initial operation of a parallel-type concrete plug. Defining the operating environmental and loading conditions of the plug was particularly challenging due to the uncertainties in the conditions of the overlying muckpile. This was approached by establishing a range of scenarios and checking the designed plug for energy absorption capacity relative to possible resultant inrushes. Plug design was advanced using a novel approach for concrete mass pour, incorporating filler holes from an overlying drift, to fill the core between front and back mesh-reinforced fibrecrete form walls. To control the risk of thermal cracking and for sulphate resistance, a project-specific concrete mix was developed which had high flowability to ensure complete and tight filling. Post-construction testing included a full reservoir fill, during which the plug maintained its integrity but exhibited seepage above target rates. A pressure grouting program was conducted which reduced the rate significantly. This case study provides useful information for operations in a similar situation, along with key learnings and recommendations from the process.